The Importance of Plato’s Art Criticism - Rymar, Dariusz (Folia Philosophica, 2024)
The article opens by outlining the aporias present in contemporary theoretical approaches to art, including the stereotypical view of Plato’s alleged hostility towards art. What follows is a synthetic overview of the state of artistic culture, taking into account controversial theoretical perspectives and laying the groundwork for demonstrating the relevance of examining Plato’s insights. Further, the article discusses the concept of “basanistic pedagogy” (W.H.F. Altman), characterized by intellectual provocations designed to enhance critical thinking skills. Building on this foundation, the article analyzes the argumentation from The Republic and Philebus, focusing on cognitive competencies and the potential for formulating reliable evaluations of artworks. Further examination of Laws addresses the notion of “true judges” of art, emphasizing the substantive and moral qualifications of art critics. The analysis then shifts to the treatment of aesthetic pleasures in Laws and the formal approach to beauty in Hippias Major. Based on the collected arguments, the article elucidates the reasons for the ambiguity in Plato’s statements on art. The conclusion reflects on the academic tradition of educating artists, highlighting the potential for a constructive interpretation of Platonic reflections on art.